1993
DOI: 10.1002/j.1460-2075.1993.tb05902.x
|View full text |Cite
|
Sign up to set email alerts
|

The lux autoinducer regulates the production of exoenzyme virulence determinants in Erwinia carotovora and Pseudomonas aeruginosa.

Abstract: Erwinia carotovora and Pseudomonas aeruginosa secrete exoenzymes that contribute to the pathogenesis of plant and mammalian infections respectively. E.carotovora mutants defective in synthesis of the pectinase, cellulase and protease exoenzymes were isolated and classified into two groups. Group 2 mutants were found to be defective in the production of a small freely diffusible molecule, N‐3‐(oxohexanoyl)‐L‐homoserine, lactone (HSL), and were avirulent. Addition of exogenous HSL to these group 2 mutants restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
342
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(354 citation statements)
references
References 27 publications
7
342
0
5
Order By: Relevance
“…Indeed, only the expression of pelA and pelB genes is significantly decreased in an expI mutant. The behaviour of the E. chrysanthemi expI mutant is therefore different from that of the E. carotovora expI mutant, which produces only low levels of Pel (Jones et al, 1993). Such a difference between the two species might be explained by the existence of only one detectable acyl-HSL produced by E. carotovora (OHHL), whereas several pheromones are produced by E. chrysanthemi.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, only the expression of pelA and pelB genes is significantly decreased in an expI mutant. The behaviour of the E. chrysanthemi expI mutant is therefore different from that of the E. carotovora expI mutant, which produces only low levels of Pel (Jones et al, 1993). Such a difference between the two species might be explained by the existence of only one detectable acyl-HSL produced by E. carotovora (OHHL), whereas several pheromones are produced by E. chrysanthemi.…”
Section: Discussionmentioning
confidence: 87%
“…The genes aepA and aepH have been described as activators of extracellular enzyme synthesis (Murata et al, 1991;Liu et al, 1993). Other E. carotovora mutants with decreased pectinase production are affected in the expI-expR locus (also called rexI/rexR or carI/carR or hslI ), which is responsible for the cell density control of extracellular enzyme production (Jones et al, 1993;Pirhonen et al, 1993). The ExpI-ExpR couple is homologous to the LuxI-LuxR system of Vibrio fischeri (Meighen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Mutants defective in production of OHHL were also defective in synthesis of the pectinase, cellulase, and protease exoenzymes. These mutants failed to induce soft rot disease in potato tubers (4). It was found that the expI gene, which is homologous to the luxI gene of Vibrio fischeri, encodes AI production in E. carotovora.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, AIs have been identified in several Gram-negative bacteria. AIs are involved in the regulation of a range of biological functions, including Ti plasmid conjugal transfer in Agrobacterium tumefaciens (3), induction of virulence genes in Erwinia carotovora, Erwinia chrysanthemi, Erwinia stewartii, Pseudomonas aeruginosa, Pseudomonas solanacearum, and Xenorhabdus nematophilus (4)(5)(6)(7)(8)(9)(10)(11)(12), regulation of antibiotic production in Pseudomonas aureofaciens and E. carotovora (10,13), regulation of swarming motility in Serratia liquefaciens (14), and biofilm formation in Pseudomonas fluorescens and P. aeruginosa (15,16). Many more bacterial species are known to produce AIs, but the relevant biological functions have not yet been established (17)(18)(19).…”
mentioning
confidence: 99%
“…Response to DF indicates the effect of added DSF on the level of endoglucanase produced by the strains; ¹ indicates less than a twofold increase; þþ indicates at least a 10-fold increase. production of enzymes in other bacteria such as the plant pathogen Erwinia carotovora (Jones et al, 1993;Pirhonen et al, 1993), it was of interest to examine the kinetics of DSF accumulation in relation to enzyme synthesis. Cultures of Xcc strains 8004 containing pIJ3077 (a plasmid with a correctly orientated Tn5lac transcriptional fusion reporter in the prtA protease gene) and 8004 containing pIJ3033 (which is pIJ3020 with a Tn5lac insertion in rpfF ) were inoculated at low density and, at intervals, measurements were made of bacterial growth, ␤-galactosidase and DSF levels.…”
Section: Production Of Dsf In Xcc Culturesmentioning
confidence: 99%